2006
DOI: 10.1016/j.jmb.2005.11.067
|View full text |Cite
|
Sign up to set email alerts
|

Multiple U2AF65 Binding Sites within SF3b155: Thermodynamic and Spectroscopic Characterization of Protein–Protein Interactions among pre-mRNA Splicing Factors

Abstract: Essential, protein-protein complexes between the large subunit of the U2 small nuclear RNA auxiliary factor (U2AF65) with the splicing factor 1 (SF1) or the spliceosomal component SF3b155 are exchanged during a critical, ATP-dependent step of pre-mRNA splicing. Both SF1 and the N-terminal domain of SF3b155 interact with a U2AF homology motif (UHM) of U2AF65. SF3b155 contains seven tryptophan-containing sites with sequence similarity to the previously characterized U2AF65-binding domain of SF1. We show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
110
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(127 citation statements)
references
References 59 publications
15
110
0
Order By: Relevance
“…The structures of individual SF3b155 ULMs bound to UHMs, including those of SPF45 and CAPERα ( Fig. 2E,F; (Thickman et al 2006). Consistent with findings for the U2AF 65 UHM, a battery of methods including size exclusion chromatography, amino acid analysis, and ITC show that two CAPERα UHMs concurrently bind the SF3b155 ULMcontaining region under saturating conditions (Loerch et al 2014).…”
Section: Potential Functions Of Multiple Functions Of Multiple Sf3b15supporting
confidence: 77%
See 2 more Smart Citations
“…The structures of individual SF3b155 ULMs bound to UHMs, including those of SPF45 and CAPERα ( Fig. 2E,F; (Thickman et al 2006). Consistent with findings for the U2AF 65 UHM, a battery of methods including size exclusion chromatography, amino acid analysis, and ITC show that two CAPERα UHMs concurrently bind the SF3b155 ULMcontaining region under saturating conditions (Loerch et al 2014).…”
Section: Potential Functions Of Multiple Functions Of Multiple Sf3b15supporting
confidence: 77%
“…Alternatively, the SF1 ULM is recognized by the UHM of the KIS/UHMK1, which directs phosphorylation of an SF1 SPSP motif (Manceau et al 2006(Manceau et al , 2008. Soon thereafter, we and others noticed seven ULM-like repeats in the Nterminal region of the SF3b155 subunit of the U2 snRNP, and confirmed that five of these putative SF3b155 ULMs detectably associate with UHMs (Thickman et al 2006;Corsini et al 2007Corsini et al , 2009Loerch et al 2014). The SF3b155 ULM-U2AF 65 UHM complex is likely to assist SF1 displacement and stable association of the U2 snRNP during spliceosome assembly, whereas other UHM-containing splicing factors may regulate this process.…”
Section: A Limited Cohort Of Established "U2af Ligand Motifs"supporting
confidence: 76%
See 1 more Smart Citation
“…2d). In contrast, Bud13p might not only bind to Snu17p within the RES complex but also engage in interactions with other proteins, possibly via the canonical mode, in agreement with the ability of single ULMs to bind to different UHMs 21,23 .…”
Section: Discussionmentioning
confidence: 86%
“…Often, however, cooperativity is of the 'copy-and-enhance' type, in which multiple identical or similar units of low affinity act together to enable an elevated total affinity 2,23 . This mode of cooperativity is used in PUF60-and U2AF65-concomitant binding to SF3b155 to cooperatively recruit U2 snRNP 44 , as well as in splicing factor 1 and U2AF heterodimer association with the 3′ splice site 43 .…”
Section: Discussionmentioning
confidence: 99%